Chronic Ethanol Consumption Alters All-Trans-Retinoic Acid Concentration and Expression of Their Receptors on the Prostate: A Possible Link Between Alcoholism and Prostate Damage - Fontanelli, Beatriz A.F. [UNESP]; Chuffa, Luiz G.A. [UNESP]; Teixeira, Giovana R. [UNESP]; Amorim, João P.A. [UNESP]; Mendes, Leonardo O. [UNESP]; Pinheiro, Patricia F.F. [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Pereira, Sérgio [UNESP]; Fávaro, Wagner J. [UNESP]; Martins, Otávio A. [UNESP]; Mello Júnior, Wílson de [UNESP]; Martinez, Marcelo; et al. (Wiley, 2013)
Background: Ethanol (EtOH) alters the all-trans-retinoic acid (ATRA) levels in some tissues. Retinol and ATRA are essential for cell proliferation, differentiation, and maintenance of prostate homeostasis. It has been suggested that disturbances in retinol/ATRA concentration as well as in the expression of retinoic acid receptors (RARs) contribute to benign prostate hyperplasia and prostate cancer. This study aimed to evaluate whether EtOH consumption is able to alter retinol and ATRA levels in the plasma and prostate tissue as well as the expression of RARs, cell proliferation, and apoptosis index. Methods: All animals were divided into 4 groups (n = 10/group). UChA: rats fed 10% (v/v) EtOH ad libitum; UChACo: EtOH-naïve rats without access to EtOH; UChB: rats fed 10% (v/v) EtOH ad libitum; UChBCo: EtOH-naïve rats without access to EtOH. Animals were euthanized by decapitation after 60 days of EtOH consumption for high-performance liquid chromatography and light microscopy analysis. Results: EtOH reduced plasma retinol concentration in both UChA and UChB groups, while the retinol concentration was not significantly different in prostate tissue. Conversely, plasma and prostate ATRA levels increased in UChB group compared with controls, beyond the up-regulation of RARβ and -γ in dorsal prostate lobe. Additionally, no alteration was found in cell proliferation and apoptosis index involving dorsal and lateral prostate lobe. Conclusions: We conclude that EtOH alters the plasma retinol concentrations proportionally to the amount of EtOH consumed. Moreover, high EtOH consumption increases the concentration of ATRA in plasma/prostate tissue and especially induces the RARβ and RARγ in the dorsal prostate lobe. EtOH consumption and increased ATRA levels were not associated with cell proliferation and apoptosis in the prostate. © 2012 by the Research Society on Alcoholism.
Keywords: All-Trans-Retinoic acid; Ethanol; Prostate; Retinoic acid receptor; Retinol; alcohol; retinoic acid; retinoic acid receptor; alcohol consumption; alcoholism; animal experiment; animal tissue; apoptosis; apoptosis index; blood analysis; cell proliferation; cellular parameters; controlled study; food intake; high performance liquid chromatography; immunohistochemistry; male; microscopy; nick end labeling; nonhuman; priority journal; prostate disease; protein expression; rat; Alcohol Drinking; Animals; Apoptosis; Cell Proliferation; Central Nervous System Depressants; Male; Rats; Rats, Wistar; Receptors, Retinoic Acid; Tretinoin; Animalia; Rattus